2014
DOI: 10.1111/febs.12613
|View full text |Cite
|
Sign up to set email alerts
|

Understanding polyspecificity within the substrate‐binding cavity of the human multidrug resistance P‐glycoprotein

Abstract: Human P-glycoprotein (P-gp) controls drugs bioavailability by pumping out of the cells many structurally-unrelated drugs. The x-ray structure of the mouse P-gp ortholog was solved with two SSS- and one RRR-enantiomers of the selenohexapeptide inhibitor QZ59, found within the putative drug-binding pocket of the membrane domain outer leaflet. This offered the first opportunity to localize the well-known H- and R- drug-substrate sites in light of QZ59 inhibition mechanisms that were characterized here in cellulo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 32 publications
3
34
0
1
Order By: Relevance
“…The candidate residues identified using this approach were in broad agreement with those identified from docking and MD simulation based studies [20,34,35]. Another investigation using a large number of P-gp isoforms adopted a different approach using arginine enhancer mutations to identify residues within the translocation pathway [36].…”
Section: Discussionsupporting
confidence: 62%
“…The candidate residues identified using this approach were in broad agreement with those identified from docking and MD simulation based studies [20,34,35]. Another investigation using a large number of P-gp isoforms adopted a different approach using arginine enhancer mutations to identify residues within the translocation pathway [36].…”
Section: Discussionsupporting
confidence: 62%
“…The mouse embryonic fibroblasts, of either wild-type (NIH3T3) or overexpressing Pgp (NIH3T3 ABCB1 ) [39], were maintained under the same conditions. The cell culture media were drug supplemented with either 0.75 mg/mL G418 (HEK293 ABCG2 ), 200 μg/mL hygromycin B (HEK293 pcDNA5 and HEK293 ABCC1 ) or 60 ng/mL colchicin (NIH3T3 ABCB1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 10D) although not precisely at the minima indicated in the PMFs. Studies by Lugo et al 37 and Martinez et al 38 have shown that the TM pore of P-gp is large enough to accommodate multiple substrates/molecules and thus it is plausible for both Hoechst 33342 and Rhodamine 123 to occupy the TM pore.…”
Section: The Effect Of Starting Structure On Substrate Bindingmentioning
confidence: 99%
“…In recent years, a number of computational approaches have been used in an attempt to characterize potential substrate binding sites in P-gp. These include molecular docking and pharmacophore mapping studies [36][37][38][39][40] . In two independent studies, Ferreira et al 36 and Tarcsay and Keserű 37 examined the interaction of various P-gp substrates such as Rhodamine 123, vinblastine, verapamil and Hoechst 33342 with P-gp using molecular docking studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation